Effectiveness of infant massage therapy on weight gain in low birth weight infants: A literature review - Ni Made Sulastri; Ni Wayan Armini; Ni Komang Erny Astiti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Low birth weight infants (LBWI) are at risk of growth disorders and neonatal complications. Baby massage therapy is a non-pharmacological intervention believed to improve infant growth and weight gain. Purpose: To examine and analyze the research findings related to the effectiveness of infant massage therapy on weight gain in low-birth-weight infants Method: This literature review analyzed articles from Google Scholar, PubMed, and ScienceDirect published between 2021–2026. Studies that focused on infant massage therapy and weight gain in underweight or premature infants were included. The inclusion criteria are described in this article. Results: The analyzed studies showed that infant massage therapy promotes weight gain in underweight and premature infants. Massage increases activity of the vagus nerve, which in turn boosts digestion, nutrient absorption, sleep quality, and milk production in infants. Other benefits include better physiological stability, less stress and better bonding between mother and baby. Conclusion: Infant massage stimulates the parasympathetic nervous system and maintains the production of growth hormone, thus promoting the absorption of nutrients and the growth of infants. The results show infant massage therapy is safe, effective and cost-efficient.